Hubungan Erodibilitas Tanah Terhadap Erosi pada Lahan Bekas Penambangan Batubara: Relationship of Soil Erodibility to Erosion in Ex-Coal Mining Land - Doli Jumat Rianto; Aji Marwadi (LPPM Universitas Mataram, 2023)
The reclamation area on ex-coal mining land is very vulnerable to erosion. Soil vulnerability comes from the physical properties of the soil, the ease with which it erodes, and the topographical conditions. Erosion occurs in open areas and little overgrown with vegetation. However, this condition is of course a fundamental consideration of the factors that influence erosion. This type of research is a descriptive quantitative research, obtained from the results of empirical calculations to determine the magnitude of erosion and the correlation between erodibility and erosion variables using Smart PLS 3, at a confidence level of 5%. The results showed that the average amount of erosion on each reclamation land was 23.61 tons/ha/year with a moderate Erosion Hazard Level (TBE), and the results of the correlation test showed that there was a significant relationship between erosion and the factors that affect soil erodibility. such as permeability, soil grain size, and soil organic matter content, while topographical conditions are not so significant on the amount of erosion on reclamation land, it is suspected that fine clay soil texture plays a role in reducing the erosion rate.